Secrecy capacity analysis of bi-static backscatter communication systems - Phung Ton That; Duy-Hung Ha; Hong-Nhu Nguyen (Institute of Advanced Engineering and Science, 2022)
The rapid adoption of battery-free internet-of-things (IoT) sensors in multiple environments ranging from agriculture to wildlife surveillance, has seen increased research interest in backscatter communication (BSC) technology. BSC is viewed as a potential technology to enable the further spread of sustainable battery-free IoT applications in environments and scenarios where bulkier-sized battery-powered IoT devices would be unsuitable. In this study, we investigate the secrecy capacity of a bi-static BSC network in the presence of a malicious eavesdropper. The proposed BSC system consists of a reader, multiple backscatter devices, and an eavesdropper. We derive closed-form strictly positive secrecy capacity (SPSC) expressions and ergodic secrecy capacity (ESC) expressions for the BSC reader. Monte Carlo simulations verify the exact capacity expressions.